2019
DOI: 10.1002/anie.201901922
|View full text |Cite
|
Sign up to set email alerts
|

C‐Terminal Bioconjugation of Peptides through Photoredox Catalyzed Decarboxylative Alkynylation

Abstract: We report the first decarboxylative alkynylation of the C‐terminus of peptides starting from free carboxylic acids. The reaction is fast, metal‐free, and proceeds cleanly to afford alkynylated peptides with a broad tolerance for the C‐terminal amino acid. By the use of hypervalent iodine reagents, the introduction of a broad range of functional groups was successful. C‐terminal selectivity was achieved by differentiation of the oxidation potentials of the carboxylic acids based on the use of fine‐tuned organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 86 publications
(35 reference statements)
1
76
0
Order By: Relevance
“…The chloromethyl radical generation by photoredox catalysis is a useful strategy for cyclopropanation [58]. Most photoredox catalyzed, decarboxylative generations of carbon-centered radicals are based on the formation of "stabilized" α-amino [59][60][61][62][63][64][65] or benzyl [66][67][68][69][70] radical species. However, the generation of unstabilized alkyl radical species is also known [71][72][73][74].…”
Section: Resultsmentioning
confidence: 99%
“…The chloromethyl radical generation by photoredox catalysis is a useful strategy for cyclopropanation [58]. Most photoredox catalyzed, decarboxylative generations of carbon-centered radicals are based on the formation of "stabilized" α-amino [59][60][61][62][63][64][65] or benzyl [66][67][68][69][70] radical species. However, the generation of unstabilized alkyl radical species is also known [71][72][73][74].…”
Section: Resultsmentioning
confidence: 99%
“…[7] Through photoredox catalysis, selective C-terminal functionalization has been achieved due to the difference in oxidation potential relative to side-chain residues (Scheme 1 c). [8] Esterification of carboxylic acids is a well-established prodrug strategy and recently Raines et al demonstrated how esterification with diazo compounds can enable the translocation of a putative therapeutic agent across the plasma membrane (Scheme 1 d). [9] Peptides and proteins are already highly complex molecules with several stereocenters, and adding additional complexity through a stereoselective bioconjugation strategy could lead to higher selectivity towards the chiral environment present in receptors.…”
mentioning
confidence: 99%
“…[19] Zeitler and coworkers later showed that the reported conditions led to the incorporation of only three diphenylamine units. [23] Substitution with electron-withdrawing groups led to 4ClDPAIPN (3b)a nd 4BrDPAIPN (3c). [23] Substitution with electron-withdrawing groups led to 4ClDPAIPN (3b)a nd 4BrDPAIPN (3c).…”
mentioning
confidence: 99%
“…Using TIPS-EBX (1a,T IPS = triisopropylsilyl) and Ir catalyst 4 led to decomposition of the reagent, which was faster than the desired alkynylation. [23] For 2c,w eo bserved full consumption of the catalyst, indicating stability issues. [10j, 24] Thestronger oxidant 4ClCzIPN (2b) afforded 89 %y ield.…”
mentioning
confidence: 99%
See 1 more Smart Citation